2011
DOI: 10.1371/journal.pone.0016789
|View full text |Cite
|
Sign up to set email alerts
|

Transplanted Human Amniotic Membrane-Derived Mesenchymal Stem Cells Ameliorate Carbon Tetrachloride-Induced Liver Cirrhosis in Mouse

Abstract: BackgroundHuman amniotic membrane-derived mesenchymal stem cells (hAMCs) have the potential to reduce heart and lung fibrosis, but whether could reduce liver fibrosis remains largely unknown.Methodology/Principal FindingsHepatic cirrhosis model was established by infusion of CCl4 (1 ml/kg body weight twice a week for 8 weeks) in immunocompetent C57Bl/6J mice. hAMCs, isolated from term delivered placenta, were infused into the spleen at 4 weeks after mice were challenged with CCl4. Control mice received only sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
103
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(108 citation statements)
references
References 48 publications
3
103
0
2
Order By: Relevance
“…Furthermore, more extensive studies documented the various differentiations of hAECs into neuron, astrocytes, pancreatic cells, cardiomyocytes, myocytes, osteocytes and adipocytes. 30 Human amniotic membrane-derived MSCs (AM-hMSCs) Amniotic membrane-human MSCs are isolated from amniotic membrane 8,16,24,26 and named AM-hMSCs. AM-hMSCs can be obtained after in vitro culture of term amnion.…”
Section: Stem Cell Characteristics Of Amniotic Membrane/ Fluid-derivementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, more extensive studies documented the various differentiations of hAECs into neuron, astrocytes, pancreatic cells, cardiomyocytes, myocytes, osteocytes and adipocytes. 30 Human amniotic membrane-derived MSCs (AM-hMSCs) Amniotic membrane-human MSCs are isolated from amniotic membrane 8,16,24,26 and named AM-hMSCs. AM-hMSCs can be obtained after in vitro culture of term amnion.…”
Section: Stem Cell Characteristics Of Amniotic Membrane/ Fluid-derivementioning
confidence: 99%
“…21,32 In terms of differentiation potential, AMhMSCs were shown to differentiate in culture toward different cell types such as adipogenic, chondrogenic, osteogenic, skeletal-and cardio-myogenic, endothelial cells, hepatocyte-like cells and neuroglial cells. 33 Zhang et al 26 have reported that the transplantation of AM-hMSCs significantly decreased hepatic fibrosis and progression of CCl 4 -induced cirrhosis, thereby providing a new approach for the treatment of fibrotic liver disease. In addition, when transplanted in rat heart, they were also shown to survive and to achieve cardiac differentiation without immunological rejection.…”
Section: Stem Cell Characteristics Of Amniotic Membrane/ Fluid-derivementioning
confidence: 99%
“…Studies show that MSC are capable of inhibiting apoptosis in kidney, liver and brain injuries (30,(131)(132)(133). Recent evidence shows that this is done through increasing prosurvival factors as Akt expression in injured cells (55), BDNF and growth factors as IGF, VEGF and HGF expression which inhibit apoptosis and stimulate cell proliferation (134,135).…”
Section: Anti-apoptotic Factorsmentioning
confidence: 99%
“…The multipotent differentiation capacity of human amniotic membrane-derived mesenchymal stem cells (hAM-MSCs) has been reported recently, and studies support their candidacy as a suitable source for cell-based therapy [14][15][16][17][18]. Analogous to bone marrow-derived cells, hAM-MSCs exhibit self-renewal ability, strong immunosuppressive function, freedom from ethical concerns, and easy accessibility and can be induced to various cell types, including the hepatic lineage [19].…”
Section: Introductionmentioning
confidence: 99%